DIGITAL FINANCE SERVICE: PENINGKATAN LITERASI KEUANGAN BERBASIS DIGITAL PADA UMKM BANGUNTANI MENUJU KINERJA USAHA BERKELANJUTAN - Yahya, Adibah; Nurastuti, Preatmi; Nurjanah, Rina; Hartini, Estuti Fitri; Mandala, Kesha Meiva (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economic growth, but business sustainability is a challenge, especially due to the low understanding of financial digitalisation. Utilisation of Digital Financial Services is important to facilitate financial inclusion and support the competitiveness of MSMEs in the era of technological revolution. This community service activity aims to improve digital-based financial literacy in Banguntani MSMEs so that they are able to implement digital finance in their business processes, towards sustainable business performance. The methods used are socialisation, interactive training with a hands-on approach or "Learning While Practising", and direct assistance. Impact measurement was conducted through the comparison of pre-test and post-test scores. The results showed an increase in digital financial literacy of 47.6%. This activity succeeded in transforming the skills of Banguntani MSMEs, equipping them with the ability to record accurate finances, adopt QRIS, and understand access to legal capital, which are prerequisites for optimal and sustainable business performance.